2009
DOI: 10.4155/fmc.09.9
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Receptor Modulators and Their Therapeutic Potential

Abstract: Taking into account the great number of pathological conditions related to ghrelin, and the discovery of several compounds able to modulate the ghrelin receptor, its importance in the field of medicinal chemistry research is set to increase significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 127 publications
0
9
0
Order By: Relevance
“…On these bases, several research groups discovered various chemotypes able to modulate GHS-R1a [335]. Worth of note are EP-51389 (( B ), Scheme 1 ) and its derivative JMV-1843 (EP-1572, AESZ-130) (( 5 ), Scheme 1 ), that originated the widest series of GHS-R1a ligands.…”
Section: Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On these bases, several research groups discovered various chemotypes able to modulate GHS-R1a [335]. Worth of note are EP-51389 (( B ), Scheme 1 ) and its derivative JMV-1843 (EP-1572, AESZ-130) (( 5 ), Scheme 1 ), that originated the widest series of GHS-R1a ligands.…”
Section: Neuroprotectionmentioning
confidence: 99%
“…(Scheme 1 ) reports the structures and the design process of the ghrelin modulators reported in the present article. In fact, starting from JMV-1843, a series of substituted 1,2,4-triazoles, acting as agonists, partial agonists, or antagonists, were synthesized and pharmacologically evaluated, but no clear correlations between in vitro and in vivo results have been obtained [335]. …”
Section: Neuroprotectionmentioning
confidence: 99%
“…A number of small molecule ghrelin receptor antagonists have been described in the literature (see Figure ). − The vast majority of these efforts have focused on centrally acting agents targeted toward the treatment of obesity. We previously reported on a spiro-azetidino-piperidine series that was identified from high-throughput screening (HTS) of our corporate file .…”
mentioning
confidence: 99%
“…This prompted the research of ghrelin receptor antagonist/inverse agonists as antiobesity agents. After the discovery of the ghrelin peptidic antagonist [d-Lys3]GHRP-6, able to reduce food intake and BW gain in lean, ob/ob (leptin-deficient) and DIO mice, several classes of nonpeptidic ghrelin receptor antagonists [75,76] showed promising in vivo activities as antiobesity agents (preclinical researches) [75]. However, results obtained in the presence of some ghrelin antagonists/inverse agonists showed that the effect on BW and feeding not always correlates with the in vitro actions on ghrelin receptor.…”
Section: Ghrelin Antagonists/inverse Agonistsmentioning
confidence: 99%